AKIBAT HUKUM PEMBUBARAN BP MIGAS - Dian Aries Mujiburohman (Fakultas Hukum Universitas Gadjah Mada, 2013)
This paper discusses the Constitutional Court Decision Number 36/PUU-X/2012 concerning judicial review of Law Number 22 Year 2001 on Oil and Gas, which contains the dissolution judgment Oil and Gas Executive Agency (BP Migas). This study focuses on meaning of the State Control over Oil and Natural as resources which is considered to be degraded by the presence of BP Migas and the legal consequences after the dissolution of BP Migas, the impact of the dissolution to institution of the above mentioned, BP Migas, the contract of cooperation and the status of their employees. Tulisan ini membahas tentang Putusan Mahkamah Konstitusi Nomor 36/PUU-X/2012 perihal Pengujian Undang-Undang Nomor 22 Tahun 2001 tentang Minyak dan Gas Bumi, putusan yang berisi pembubaran Badan Pelaksana Minyak dan Gas Bumi (BP Migas), kajian ini menitikberatkan pada makna Penguasaan Negara atas Sumber Daya Alam Migas yang dianggap telah terdegradasi oleh keberadaan BP Migas dan apa akibat hukum pasca pembubaran BP Migas terhadap kelembagaan, kontrak kerja sama, status pengawas BP Migas.